OPTIMALISASI PENGELOLAAN KAS RT BERBASIS DIGITAL MELALUI PELATIHAN DAN PENDAMPINGAN MICROSOFT EXCEL PADA RT 04/RW 04 BAMBU KUNING BATAM - Amrizal Amrizal; Rika Harman; Sefni Melia Putri (ASOSIASI IDEBAHASA KEPRI, 2026)
Orderly and transparent financial management of Neighborhood Associations (Rukun Tetangga/RT) is an essential factor in supporting accountability in community fund management. One of the common challenges faced by RT administrators is the continued use of manual cash-book recording systems, which may lead to recording errors, data loss, and delays in preparing financial reports. This Community Service Program (PKM) aimed to optimize digital-based RT cash management through training and mentoring on the use of Microsoft Excel for the administrators of RT 04/RW 04, Bambu Kuning, Batam. The implementation methods included initial observation, socialization, training sessions, hands-on practice, and continuous mentoring. The training materials covered the creation of digital cash books, recording of cash inflows and outflows, the application of basic Microsoft Excel formulas, and the preparation of automated cash reports. The results demonstrated an improvement in participants’ knowledge and skills in managing RT finances digitally. After participating in the program, the participants were able to record financial transactions and independently generate cash reports using Microsoft Excel. This activity had a positive impact on enhancing the efficiency of financial administration, simplifying report preparation, and promoting transparency and accountability in the management of RT funds.